2002
DOI: 10.1017/s0014479702000212
|View full text |Cite
|
Sign up to set email alerts
|

Management of Manure in Farming Systems in Semi-Arid West Africa

Abstract: The last 50 years have seen a rapid expansion of cultivated area in semi-arid areas of West Africa. This has precipitated a change from traditional fallowing to more pro-active soil fertility management techniques. Smallholder farmers employ a range of technologies to enhance soil fertility and manure is a cornerstone of many of the soil fertility management strategies they use. This paper reviews manure management by smallholder farmers. It considers factors that affect the quality of the manure used, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 15 publications
3
54
1
Order By: Relevance
“…Livestock convert vegetative plant material and residues to dung, as manure a valuable resource to maintain fertility of pasture and especially of cropland (Harris, 2002). However, the use as fertilizer often competes with the use of dung as fuel for fire as the availability of firewood is often limited (Lupwayi et al, 2000).…”
Section: Animal Feedmentioning
confidence: 99%
See 1 more Smart Citation
“…Livestock convert vegetative plant material and residues to dung, as manure a valuable resource to maintain fertility of pasture and especially of cropland (Harris, 2002). However, the use as fertilizer often competes with the use of dung as fuel for fire as the availability of firewood is often limited (Lupwayi et al, 2000).…”
Section: Animal Feedmentioning
confidence: 99%
“…Cattle dung was used by all households as manure or as a fuel, which affects the nutrient cycling in crop-livestock systems accordingly (Harris, 2002;Lekasi et al, 2003). A higher proportion being used as fuel in the midland and highland regions BW and DD.…”
Section: Animal Feed and Dung Usementioning
confidence: 99%
“…Grazing reduces land-cover by the amount determined by the grazing intensity map discussed in the previous paragraph. Grazing also affects soil fertility in that manure from grazing animals is added to the soil at a rate commensurate to the intensity of grazing on that patch [65].…”
Section: Human Land-use Modelmentioning
confidence: 99%
“…In South Africa, the use of animal manure as a source of plant nutrients is a well-established practice especially among the small-scale farming sector (Mkhabela & Materechera, 2003). As is the case elsewhere in sub-Saharan Africa (Harris, 2002), animal manure is particularly important in semi-arid areas of South Africa because the dry environment and extensive land resource for grazing allows people to keep large numbers of livestock. Experience and results of a preliminary survey of 150 households in 10 villages around Mafikeng in the North West province in 2002 revealed that large amounts of manure are available for use by the small scale farming households (S.A. Materechera, 2002, North-West University, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are other characteristics of manure, such as colour, presence of moulds, moisture content, homogeneity, texture and soil within the manure, which are traditionally used by farmers to define quality (Lekasi et al, 1998). The nutrient content of manure obtained in kraals from small-scale farmer's households is affected by many factors including the quality of feed, storage and handling conditions in the kraal, ambient temperature and moisture levels, length of exposure to the environment and other management factors Lupwayi, Girma & Haque, 2000;Harris, 2002).…”
Section: Introductionmentioning
confidence: 99%